Assessment of codependency and alexithymia within the frame of addiction risk - Feyzioğlu, Aynur; Özkars, Nesibe; Emiral, Ekin; Akan Tikici, Zeynep (Journal of Dependence, 2019)
Objective: This research aims to investigate the correlation between codependency and alexithymia with the groups that have different level of addiction vulnerability. Method: 383 students (289 women, 94 men) from Sağlık Bilimleri University participated in the study based on volunteerism and confidentiality. The socio-demographic data form, Toronto Alexithymia Scale, and Codependency Assessment Tool were used in the study. Results: Alexithymia increased while the codependency increased. Moreover, as life satisfaction increases, codependency and alexithymia are decreasing. The alexithymia and codependency scores of the substance dependent group were significantly higher than the non-use group. Likewise, alexithymia and codependency scores of individuals who reported to had experienced physical violence in childhood are significantly higher than those who did not. Conclusion: The correlation of alexithymia, which is thought to be a disorder caused by emotion regulation and cognitive processing in the literature, shows new question marks for the etiology of codependency. Mental health professionals working with codependent people should take into account the difficulties that they may have in understanding their emotions.